2006
DOI: 10.1186/bf03352630
|View full text |Cite
|
Sign up to set email alerts
|

Cooling rate corrected paleointensities from the Xitle lava flow: Evaluation of within-site scatter for single spot-reading cooling units

Abstract: The historic Xitle lava, which covers a great part of southern Mexico City, is one of the most studied (magnetically) volcanic unit worldwide. Studies include detailed paleomagnetic and paleointensity investigations, which have documented an enigmatic within-flow variation of absolute paleointensity first recognized in the decade of 1960s. However, attempts to find possible explanations in terms of physical/magnetic parameters or geomagnetic effects have been unsatisfactory. As an effort to understand the over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 21 publications
1
15
0
1
Order By: Relevance
“…Attempts to find possible correlation between these variations and some physical/magnetic parameters failed, and explanations given were unsatisfactory. Recently, Leonhardt et al (2006) and Morales et al (2006c) recognized the importance that CR could have on within-site scatter of paleointensity values observed on vertical profiles and experimentally demonstrated that the dispersion found is largely reduced applying the CR correction.…”
Section: Introductionmentioning
confidence: 98%
“…Attempts to find possible correlation between these variations and some physical/magnetic parameters failed, and explanations given were unsatisfactory. Recently, Leonhardt et al (2006) and Morales et al (2006c) recognized the importance that CR could have on within-site scatter of paleointensity values observed on vertical profiles and experimentally demonstrated that the dispersion found is largely reduced applying the CR correction.…”
Section: Introductionmentioning
confidence: 98%
“…This effect consists of a progressive increase of TRM intensity with the decrease of the cooling rate. For laboratory cooling times this effect is significant in potteries (e.g., Fox and Aitken, 1980;Chauvin et al, 2000) and occasionally for rock samples as well (Morales et al, 2006). In order to quantify the cooling rate effect, we carried out three in-field heatings after the paleointensity measurements: (a) fast-cooling (∼1 h), (b) slow-cooling (∼20 h) and (c) fast-cooling (∼1 h) again.…”
Section: Methodsmentioning
confidence: 99%
“…et al., 1965;Bucha et al, 1970;Lee, 1975;Aitken et al, 1991;Gonzalez et al, 1997;Böhnel et al, 1997;Morales et al, 2001;Böhnel et al, 2003;Morales et al, 2006), no serious attempts have been undertaken to study the rich cultural heritage of the region. The study reported here presents the first archeointensity survey from Mesoamerica and is part of the effort to establish an archeointensity variation curve for the region.…”
Section: Introductionmentioning
confidence: 99%